Modification of the existing maximum residue levels for fluxapyroxad in various crops. (12th September 2017) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the evaluating Member States (EMS), the Netherlands and the United Kingdom, received an application from BASF SE to modify the existing maximum residue levels (MRLs) for the active substance fluxapyroxad in several crops in order to accommodate for proposed new uses in Europe and for the import of crops. According to EFSA, the data are sufficient to derive MRL proposals for all the crops assessed, except for citrus fruits other than oranges and grapefruits. Adequate analytical enforcement methods are available to control the residues of fluxapyroxad on the commodities under consideration, but additional validation data on herbal infusion and spices would be desirable. Based on the risk assessment results, EFSA concluded that the proposed uses on various crops of fluxapyroxad and the use authorised in Brazil on oranges and grapefruits for which import of crops has been requested, will not result in a consumer exposure exceeding the toxicological reference values and therefore are unlikely to pose a consumer health risk.